From anxiety to coping: Understanding psychological distance and coping skills for climate change and COVID-19 in 10-12-year-old children. - Geertje Schuitema; Anthea Lacchia (PLoS ONE)
Children worldwide experience climate anxiety, defined as a chronic fear of environmental catastrophe. Following other scholars who sought comparison between the perceived risks and our collective responses with the COVID-19 pandemic, as they can both be considered global crises. Children's emotional responses, psychological distance and coping strategies to climate change compared and COVID-19 are compared, using a mixed-method longitudinal study among 231 primary school children across the Republic of Ireland. Pre-pandemic and post-lock down data were collected measuring children's emotions through surveys using Likert scales and sketches. Sketching, increasingly recognised as a method for assessing emotional expression, is especially useful when language skills are limited. Results suggest that because climate change was more psychologically distant than COVID-19, it was more difficult for children to effectively use emotional-, meaning-, problem-, and relationship-focused coping strategies to deal with their climate anxiety. One important conclusion of this study is that messages and strategies used to motivate adults to take climate action may increase climate anxiety among young children. Also, relationship-focused coping strategies are underutilised to help children deal with climate anxiety, whilst these were promising coping mechanisms during the COVID-19 pandemic. Therefore, creating positive social support and collective action may help young children to cope with climate anxiety.